Ribosomal protein S6 mRNA is a biomarker upregulated in multiple sclerosis, downregulated by interferon treatment, and affected by season. (May 2014) - Parnell, Grant P; Gatt, Prudence N; McKay, Fiona C; Schibeci, Stephen; Krupa, Malgorzata; Powell, Joseph E; Visscher, Peter M; Montgomery, Grant W; Lechner-Scott, Jeannette; Broadley, Simon; Liddle, Christopher; Slee, Mark; et al.
Background: Multiple Sclerosis (MS) is an immune-mediated disease of the central nervous system which responds to therapies targeting circulating immune cells. Objective: Our aim was to test if the T-cell activation gene expression pattern (TCAGE) we had previously described from whole blood was replicated in an independent cohort. Methods: We used RNA-seq to interrogate the whole blood transcriptomes of 72 individuals (40 healthy controls, 32 untreated MS). A cohort of 862 control individuals from the Brisbane Systems Genetics Study (BSGS) was used to assess heritability and seasonal expression. The effect of interferon beta (IFNB) therapy on expression was evaluated. Results: The MS/TCAGE association was replicated and rationalized to a single marker, ribosomal protein S6 (RPS6). Expression of RPS6 was higher in MS than controls ( p <0.0004), and lower in winter than summer ( p <4.6E-06). The seasonal pattern correlated with monthly UV light index ( R =0.82, p <0.002), and was also identified in the BSGS cohort ( p <0.0016). Variation in expression of RPS6 was not strongly heritable. RPS6 expression was reduced by IFNB therapy. Conclusions: These data support investigation of RPS6 as a potential therapeutic target and candidate biomarker for measuring clinical response to IFNB and other MS therapies, and of MS disease heterogeneity.